Creating and sustaining loyalty in the recruitment industry by means of integrated marketing communication - Du Toit, Narita; Mulder, Dalme (University of the Free State, 2004)
The highly competitive market-place of today has made relationship-building pivotal in the quest for marketing success. To have a relationship with a client an integrated approach incorporating the product/service, the packaging, the distribution, the price and all communication, are needed. Integrated marketing communication has become increasingly imponant as marketers (read: communicators) seek to enhance long-term relationships with clients, rather than concentrating on once-off transactions. Communicators need to regard each point of contact with a client as an opponunity to build and to create loyalty. (Relationships are based upon value-added, reciprocal exchanges of information.) This anicle's primary objective is to ground what, within the IMC perspective, creates and maintains client loyalty and how one could optimally understand why and how clients become and stay loyal in the recruitment industry. Through the combination of grounded theory and discourse analysis, this study indicates that a communicator in the recruitment industry should attempt to integrate the totality of his/her communication to guarantee a "one voice, one-look" strategy and a holistic approach.
Keywords: Marketing; Integrated marketing communication; Communicators; Recruitment